PENGARUH CARA PENYAJIAN DAN LAMANYA WAKTU PAJANAN TERHADAP KUALITAS SUSU FORMULA ANAK-ANAK - Hoetary Tirta Amallia (Biota, 2017)
Milk is an excellent food for human life, especially in children because the ideal composition. Milk formula is made from cow’s milk instead of breast milk. Reason mother do not breast feeding mothers are not enough. Causing high nutritional value of milk is easily destroyed by microorganisms for growth and development so that in a very short time the is not very suitable for consumption.this research aims to determine the effect of manner of presentation and the length of time of exposure to the quality of children’s milk formula. Research is a descriftive analytic study using purely experiment method. Research sample of infant formula is 0-6 months whitout additional sugar by engineering random sampling. Data collection using thr primary data for the study of data analysis using ANOVA test with significant level P.value < 0,05.the results showed the average number of coliform in group A (> 700C < 2 jam) 6/100ml, B (> 700C > 2 jam) 12/100ml, C (< 700C < 2 jam) 112/100ml, dan D (< 700C > 2 jam) 764/100ml. Bivariate test result in a group  A with group C had a P.value of 0,04 while the P.value in group B and group A pick value mean of 0,012 is significant or meaningful value because the value of P.value < 0,05 means between the water temperature and length of time of exposure affect each other.of the results of this study it can be concluded the influence of water temperature and length of time of exposure. Suggested that mothers and attention to how to prepare infant formula with good quality.